The Aural Impact of Solecisms in Revelation - Best, Garrett (2021)
Scholars have proposed as many as 232 solecisms (morpho-syntactical errors) within the Greek of the Apocalypse. One of the great paradoxes of the book is its astonishing complexity expressed in such irregular Greek. While numerous scholars have sought to account for and explain the solecisms in Revelation, few have explored the aural dimension. Since the book was designed to be read aloud to early churches in Asia, it is important to investigate how irregular grammar would have affected the first hearers. This paper attempts to fill this lacuna by examining how solecisms were viewed in the ancient world and how ancients responded when lectors made mistakes in reading. This paper will then draw on the insights of ancient rhetorical handbooks to provide new insight into the irregular grammar of Revelation.
Keywords: solecisms; aurality; Apocalypse; Revelation